2018
DOI: 10.1088/1757-899x/361/1/012007
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between some materials composites in the shock wave attenuation and anti-detonation property

Abstract: Abstract. Comparing the anti-detonation property and shock wave attenuation law of the single material structures, composite material structures and sandwich material structures are simulated by AUTODYN. The simulation on the structures with different combination show that, the aramid fiber material as base material in touched with the explosives, can greatly reduce the shock wave in identification board. For different material structures of the attenuation rule of shock wave, numerical simulation results show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…At present, the widely used flameproof materials are aluminum foam and polyurethane plastic. Tian Jet al [36] studied the dynamic mechanical properties and knock resistant structure of aluminum foam, and found that aluminum foam can effectively reduce the overpressure of secondary shock wave, and brittle aluminum foam can change the shape of shock wave and greatly reduce the peak stress of shock wave. Wang YG et al [37] studied the attenuation characteristics of shock wave of aluminum foam under explosive load, and found that aluminum foam had constitutive viscous effect, which would lead to absorption and dispersion of shock wave during propagation, and the attenuation of shock wave was further intensified due to the existence of chase unloading.…”
Section: Flameproof Devicementioning
confidence: 99%
“…At present, the widely used flameproof materials are aluminum foam and polyurethane plastic. Tian Jet al [36] studied the dynamic mechanical properties and knock resistant structure of aluminum foam, and found that aluminum foam can effectively reduce the overpressure of secondary shock wave, and brittle aluminum foam can change the shape of shock wave and greatly reduce the peak stress of shock wave. Wang YG et al [37] studied the attenuation characteristics of shock wave of aluminum foam under explosive load, and found that aluminum foam had constitutive viscous effect, which would lead to absorption and dispersion of shock wave during propagation, and the attenuation of shock wave was further intensified due to the existence of chase unloading.…”
Section: Flameproof Devicementioning
confidence: 99%